Validation of a symphysis-fundal height chart developed for pregnancy complicated by diabetes and hyperglycemia: An observational study - De Sousa Basso, Neusa Aparecida [UNESP]; Morceli, Glilciane [UNESP]; Costa, Roberto [UNESP]; Dias, Adriano [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema Mattos Paranhos [UNESP] (Springer Nature, 2016)
Background: The present study validates a symphysis-fundal height chart (SFH-chart) for pregnant women with type 2 diabetes mellitus (DM2), gestational diabetes mellitus (GDM) and mild gestational hyperglycemia (MGH) attending at the Diabetes and Pregnancy Reference Service of the Botucatu Medical School, UNESP, Brazil. Methods: A cross-sectional study was carried out to evaluate the performance of the specific FHC in predicting small (SGA) and large (LGA) for gestational age newborns (NB). We evaluated 206 pregnant women with DM2, GDM or MGH and their NB. The last symphysis-fundal height measure, taken at birth, was used to determine the sensitivity index (Sens), specificity index (Spe), positive prediction value (PPV), negative prediction value (NPV) and accuracy in predicting SGA and LGA. The gold standard was the Lubchenco birth weight/gestational age ratio evaluated at birth. Results: The mothers showed adequate glycemic control; 91.3 % of all pregnant women achieved HbA1c < 6,5 % in the third trimester. The SFH-chart tested achieved 100 % of Sens and NPV in predicting both SGA and LGA, with accuracy of 90.3 % (85.5; 93.6) and 91.8 % (87.2; 94.8), respectively, for predicting SGA and LGA newborns. Conclusions: The Basso SFH-chart showed high performance in predicting both SGA and LGA newborns of DM-2, GDM and MGH mothers, with better performance than the national reference SFH-chart. These findings support the internal validation of the Basso SFH-chart, which may be implemented in the prenatal care of the Diabetes and Pregnancy Reference Service-Botucatu Medical School/UNESP.
Keywords: Diabetes; Diagnostic validation; Fundal height; Hyperglycemia; Risk pregnancy